Mothers’ psychopathology and their adult offspring’s cortisol level in a Rwandan sample - Marie C. Ingabire; Serge Caparos; Eugène Rutembesa; Isabelle Blanchette (South African Journal of Psychiatry)
Background: Most studies on the influence of mothers’ trauma-related psychopathology on their offspring’s hypothalamic-pituitary-adrenal (HPA) axis functioning have been conducted in Western contexts. Furthermore, those studies have focused on the association between mothers’ post-traumatic stress disorder (PTSD) and their offspring’s HPA axis functioning. More research is needed among African populations exposed to mass violence to mitigate the intergenerational transmission of trauma.